2019
DOI: 10.1017/s2040174418001071
|View full text |Cite
|
Sign up to set email alerts
|

High maternal milk intake in the postnatal life reduces the incidence of breast cancer during adulthood in rats

Abstract: Environmental factors during perinatal life can lead to changes in the mammary gland, making it susceptible to cancer in adulthood. Breastfeeding has a special importance since it takes place at a critical period of growth and development of the newborn. We aimed to analyze if an appropriate lactation protects the offspring against mammary carcinogenesis during adult life and explore the mechanisms involved in the protective effect. One-day-old Sprague-Dawley female rats were randomly distributed in litters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…These results agree with those previously published [13]. This difference in weight gain is given exclusively by the consumption of breast milk.…”
Section: Body Weightsupporting
confidence: 93%
See 4 more Smart Citations
“…These results agree with those previously published [13]. This difference in weight gain is given exclusively by the consumption of breast milk.…”
Section: Body Weightsupporting
confidence: 93%
“…In a preliminary study we demonstrated that animals maintaining more access to maternal milk during postnatal life showed a lower incidence of mammary cancer in the adulthood [13]. This work allowed us to identify the effect over time of variations in postnatal maternal milk consumption, with a controlled animal model.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations